IDENTIFIKASI METABOLIT SEKUNDER EKSTRAK BUAH BELIMBING WULUH GEOTHERMAL NON GEOTHERMAL ACEH BESAR - Nuraskin, Cut Aja; Reca, Reca; Mardelita, Sisca (Jurnal Ilmiah Keperawatan, 2022)
Simplicia is a natural ingredient used for medicine and has not undergone any process changes and is in the form of dried material. Drying is a necessary process in maintaining the quality of a simplicia. This study aims to analyze the comparison of the amount of Ie Seu Um Geothermal and non-geothermal star fruit extracts to calculate yield value, dry weight of simplicia, drying loss, extract weight, percent yield and identify active compounds in wuluh starfruit taken from the Ie Seu Um Geothermal area. and non-geothermal Aceh Besar Aceh Province. The laboratory research method begins with oven drying. Extraction was carried out by maceration method using 96% ethanol solvent with a solvent ratio of 1:10 for 3x 24 hours. Then the extract was concentrated with a rotary evaporator, the yield value was calculated, and the phytochemical test was carried out. The identification results show that there are differences; sample dry weight, drying loss, extract weight and percent yield of geothermal and non-geothermal starfruit extract. In the ethanol extract of the wuluh starfruit Ie Seu Um Geothermal dry weight of simplicia 152 grams, drying loss 1,992.4 g, yield 52, 63%, extract weight 80 grams and the results of phytochemical screening of samples of ethanol extract of starfruit wuluh Ie Seu Um geothermal contain phenolic compounds, flavonoids, steroids, saponins. In non-geothermal star fruit ethanol extract, simplicia dry weight 150 g, drying loss 1,992.5 g, yield 3,075%, extract weight 61.5 grams and the results of phytochemical screening samples of non-geothermal star fruit ethanol extract contain phenolic compounds, flavonoids, steroids , saponins.. In conclusion, the weight of the extract and the yield of the ethanol extract of the bilimbi wuluh geothermal fruit is higher than that of the non-geothermal.